Quality of ultrasound images by midwives implementing ultrasound scanning services during antenatal clinics within selected healthcare facilities of Zambia - Shown Haluzani; Agripa Lungu; Mweetwa Mudenda; Arnold Hamapa; Catherine Mkandawire; Abraham Kaluba; Oswell Khondowe; Mushelelwa Mutale; Karren Imasiku; Muyereka Nyirenda; Osbert Nkolola; Lackson Kasonka; et al. (WFUMB Ultrasound Open)
Background: Limited access to ultrasound services in low and middle-income countries (LMICs) prompts the development of an intensive training program for midwives. The aim of this study was to evaluate the quality of ultrasound images produced by midwives and assess their competency in gestational age assessment using femur length. Methods: A cross-sectional study conducted in 11 healthcare facilities across four districts in Zambia involved the evaluation of 928 images captured during the implementation of the Training in Ultrasound to Determine Gestational Age (TUDA) program in 2021. TUDA, collaboration under the DIPLOMATIC Study, trained 24 midwives intensively for 14 days, followed by eight weeks of supervised scanning. Image assessment utilized the Sarries four-point tool, and statistical analyses included descriptive and inferential statistics. Results: Midwives achieved an 87.95 % competency level in basic ultrasound scans for gestational age determination using femur length. Assessment by four evaluators showed an average proportion of good-quality images also at 87.95 %. There were no statistically significant differences among assessors, indicating consistency in evaluations. Trainers and radiographers exhibited different average proportions of good-quality images at 91.5 % and 83.9 %, respectively, with no statistically significant differences observed between them.Furthermore, analysis of image quality revealed significant variation among different facilities. Specifically, in Chipata, 24.32 % of scans were classified as poor quality, while in George Clinic, only 2.30 % were considered poor quality. A Chi-square test indicated a substantial correlation between health facility and image quality (χ2 = 15.99, p = 0.025). However, no significant correlations were found between image quality and factors such as work experience, age group, or gender. Conclusion: This study provides critical evidence for successfully training midwives to competent produce high-quality ultrasound images for determining gestational age. These findings are essential for guiding interventions aimed at enhancing ultrasound service delivery and ensuring consistent, high-quality healthcare outcomes, because this is critical for effective prenatal care in Zambia. This has high potential to improve prenatal care. Recommendation: Zambia needs to train more midwives to provide routine ultrasound services during Antenatal Care (ANC) which may ultimately reduce preterm and still births. We recommend the inclusion of ultrasound scanning in-service and pre-service training and establishment of standardized protocols and guidelines for ultrasound scanning services during antenatal clinics.